KARAKTERISTIK TINGKAT KEBUGARAN KARDIORESPIRASI SISWA KELAS 6 SD DI DESA MENGWITANI TAHUN 2014 - Nyoman Chandra Adidharma (Universitas Udayana, 2016)
Lifestyle patterns are now showing increasing obesity cases are caused by sedentary behaviors and low physical activity daily. 3 out of 10 girls and boys aged 2-15 years is approximately 31% were overweight or obese by 28%. While the research conducted in several cities of 2014 in Indonesia found the number of cases of obesity in children of primary school age reaches 12%. Obesity is the often caused by less physical activity. This study aims to investigate the characteristics of cardiorespiratory fitness level in 6th grade students in Mengwitani. This research was descriptive with cross sectional method. The number of respondents is 71 people were selected by random sampling. Measurement of cardiorespiratory fitness using the Harvard Step Test. The results obtained 55 respondents (77.5%) had a very good level of cardiorespiratory fitness. While 12 respondents (16.9%) have a good fitness level and 4 respondents (5.6%) fairly. From the results, this study can be recommended for respondents who already have high level of cardiorespiratory fitness to maintain or increase physical activity daily and it can be used as a reference for respondents who still do not have a good level of cardiorespiratory fitness to improve their cardiorespiratory fitness level.